Teachers' Perceptions of Their Own Competences in View of the Demands of the Professionalisation of the Teaching Profession - Pankowska, Dorota; Kirenko, Janusz; Samujło, Małgorzata (Przegląd Badań Edukacyjnych (Educational Studies Review), 2023)
Professionalism in the teaching profession plays a significant role in the execution of complex tasks and is based on relevant competences of varying scope and nature. The study conducted in a group of 2151 teachers from the Lubelskie Voivodeship in Poland focused on teachers’ perceptions of their professional competences in terms of their importance, difficulty and decollected. The OIP-II consists of six scales: psychomotor, sensual, imaginational, intellectual OEs, plus emotional sensitivity and emotional empathy. The participants were 116 parents-matic and transgressive. The study used a 40-item questionnaire, describing different areas of teachers’ knowledge, skills and activity, which operationalized broader groups of professional competences. Statistical analyses examined socio-demographic variables: gender, work experience, professional advancement grade, position held, and type and location of the educational establishment. The analysis of the results showed that teachers differentiate their perceptions of competences according to their nature, ranking pragmatic competences as the most important, followed by interpretive and transgressive competences, respectively. They consider the skills and activities associated with transgressive and pragmatic competences to be more difficult than those associated with interpretive competences. While assessing the mastery of competences, a similar level is observed for interpretive and pragmatic competences and a lower level for transgressive competences. On the basis of these results, it can be concluded that the teachers primarily pay attention to knowledge and practical skills related to the performance of professional tasks, with less appreciation of aspects related to interpretive and transgressive competences. This approach seems insufficient from the perspective of the ongoing professionalisation of the teaching profession and the challenges of 21st-century education.